A WOMAN’S OPPRESSION IN THE DEVIL WEARS PRADA MOVIE - Wulandari, Alifia Ghaida; Ningtyas, Tutik Ratna (Linguistics and Literature Journal, 2025)
This thesis examines the oppression and resistance of a woman in The Devil Wears Prada (2006) movie, using Virginia Woolf’s feminist theory from A Room of One’s Own (2021). This study focuses on two main issues: how oppression is depicted in the movie, and how the female main character resists the oppression. The method used in this study is qualitative, with the movie as the main source of data. The findings show that the main character, Andrea Sachs, experiences oppression through financial dependence and restrictions on her personal boundaries. Additionally, this study highlights her resistance, achieved through gaining financial independence and claiming her personal space. These acts of resistance reflect Woolf’s idea that women need both money and personal space to be free. This study is expected to provide a better understanding of women’s struggles in everyday life and contribute to literary studies on feminism, gender, identity, power, and equality. Keywords: feminist, women’s oppression, women’s resistance